Panleucogated (PLG) CD4 HIV Immune monitoring: a difference by disruption - Glencross, Deborah Kim (My University, 2022)
In 1990, the high cost of implementing a national HIV/AIDS programme was set to overwhelm South Africa’s health care budget. Not only were the prices of antiretroviral drugs prohibitive, laboratory tests needed for monitoring response to antiretroviral drugs was also unaffordable, further limiting access to care. By 1998, pleas from local clinicians to lower prices for CD4, as well as other laboratory tests like HIV viral load, were intensifying. Clinicians and local advocacy groups like Médecins Sans Frontières (MSF) and the Treatment Action Campaign (TAC) were no longer asking for, but demanding, cheaper laboratory services for HIV treatment monitoring. Respite to the emergent HIV epidemic could only come from costeffective therapies, clinical trials, and vaccine and treatment research, as well as a reliable and affordable laboratory monitoring service that was uniquely developed and appropriate for local needs. Urgent attention was needed to deliver affordable and sustainable state HIV laboratory services considering that, certainly for CD4 testing, the prevailing, conventional guide-line based CD4 testing approaches were cumbersome and costly; highly trained and skilled scientists were also expected to do the flow cytometrybased testing. It is from this background that novel PanLeucogated CD4 testing, invented and further developed by the author and her team, disrupted existing CD4 testing dogma of the time, and addressed the prevailing and emerging HIV challenges of high cost, local lack of technical skill and variable quality of the reported CD4 results. Patented and assigned to the South Africa National Health Laboratory Services, PLG CD4 was implemented into service at the start of the South African Comprehensive Care and Treatment programme in 2004, growing from a single reporting laboratory in 2002 to as many as 75 laboratories by 2010. The method was successfully implemented because it was simple to use; at the time, most personnel who were required to take on the testing, had not heard of CD4 testing, never mind flow cytometry needed to undertake testing. It was also considerably cheaper than existing methods. At the time, the potential costssavings of implementation were predicted to significantly cut HIV laboratory monitoring costs; CD4 count prices were reduced to 10% of original costs and there were millions of HIV+ patients who were predicted to present themselves for care. Work subsequently undertaken by the Glencross team, and outlined in this thesis, describes the step-bystep development and expansion of the national CD4 testing programme. The implementation of uniform systems (PLG CD4) was key to the success that followed; standardised operating procedures and quality control protocols were especially developed to meet local requirements. This tailored and specific approach has ensured reliable and harmonised CD4 reporting throughout the state laboratory service. The success of the programme has emphasised the importance of thorough due diligence and planning, as well as coordinated implementation of standardised systems appropriate for the level of care, including instruments and methodologies, that have streamlined and ensured efficient delivery of the Panleucogated CD4 testing across the South African national laboratory services Initially local, then extended to a regional scheme, Glencross and her team also introduced a locally directed external quality assessment in collaboration with the World Health Organisation, introduced as the African Regional External Quality Assessment Scheme (aka AFREQAS). The scheme, established as an independent monitoring and evaluation body for PLG CD4 users in the NHLS, subsequently grew and was expanded to support and provide external quality assessment for all CD4 laboratories across the African continent, irrespective of methodology used. Later, as requirements for additional services grew, and as an increasing number of patients accessed HIV care, new service delivery models that considered local deficiencies and strengths of service were developed. Applying these models to re-examine and appraise national services, ultimately secured nationwide service coverage, extending accessibility of CD4 counts beyond high-volume centralised testing precincts to hard-to-reach community laboratory level, but without incurring additional cost. Economically, all available resources in the national network of integrated state pathology laboratories were utilised to maximise cost savings, including use of a common laboratory management system and transport networks to facilitate transport of specimens to reference laboratories. This hierarchical approach to service delivery has been the foundation for programmatic self-determination that has ensured the success of, and underpinned, the national South African state CD4 service over the past 20 years. As gaps in service delivery later emerged, new systems to review efficiency of PLG CD4 state services were introduced that led the way for national monitoring and evaluation and timely review of, not only PLG CD4 results, but a basket of the top 25 tests offered across the national programme. Additional work described builds on the capacity and infrastructure created through rollout of CD4 testing and includes the development and integration of tests that can be ‘piggy-backed’ onto CD4 services (reflecting the versatility of protocol), as well as related ongoing training and technical capacity initiatives. A notable initiative, which has been successfully integrated into CD4 services nationally, has provided for screening of early cryptococcal infection in HIV+ patients with advanced disease. Before this milestone achievement, immune activation identified by CD38 expression on CD8 T cells, also incorporated into the PLG CD4 assay, was also shown to reliably predict response to antiretroviral therapy, offering a cheaper, more accessible alternative to more expensive HIV viral load monitoring. Last, but not least, work is presented that reveals how longitudinally assembled and curated CD4 laboratory data, collected through delivery of services over the last 17 years, has provided invaluable health programme insights into the effectiveness of programmatic delivery but additionally, enabling important epidemiological review of infectious and non-communicable disease for South Africa.
A Research report submitted in fulfillment of the requirements for the degree of Doctor of Science in Medicine (Pathology) to the faculty of Health Sciences, School of Pathology, University of the Witwatersrand, Johannesburg, 2021